2012
DOI: 10.1186/1471-2407-12-169
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 expression is associated with aggressive features of endometrial cancer

Abstract: BackgroundIncreased expression of lipocalin 2 (LCN2) has been observed in several cancers. The aim of the present study was to investigate LCN2 in endometrial cancer in relation to clinico-pathologic phenotype, angiogenesis, markers of epithelial-mesenchymal transition (EMT), and patient survival.MethodsImmunohistochemical staining was performed using a human LCN2 antibody on a population-based series of endometrial cancer patients collected in Hordaland County (Norway) during 1981-1990 (n = 256). Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
7
36
0
1
Order By: Relevance
“…These results are in accordance with Miyamoto's first report of NGAL in EC [30, 31]. The present study verified a significantly increased NGAL expression in early-grade Ishikawa EC cell line when compared to high-grade HEC-1A and KLE cell lines, suggesting it may serve as a biomarker for early-stage screening for EC.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with Miyamoto's first report of NGAL in EC [30, 31]. The present study verified a significantly increased NGAL expression in early-grade Ishikawa EC cell line when compared to high-grade HEC-1A and KLE cell lines, suggesting it may serve as a biomarker for early-stage screening for EC.…”
Section: Discussionsupporting
confidence: 93%
“…In human cancer tissues, expression of elevated levels of LCN-2, which plays a role in the intracellular transport of iron, has been detected in breast, ovarian, endometrial, intestinal, lung, pancreatic, oesophageal and gastric cancers (13)(14)(15)(16)(17)(18). In our study, levels of LCN-2 were found significantly high (P = 0.001) in all patient groups at diagnosis.…”
Section: Discussionsupporting
confidence: 52%
“…It is able to transport small lipophilic ligands, such as lipopolysaccharides (Bratt et al 1999), through the hydrophilic body fluid and acts as a bacteriostatic protein. LCN2 was first isolated from human neutrophils and has now been found to be expressed in several types of cells, including adipocytes (Zhang et al 2008), macrophages (Zhang et al 2008), brain endothelial cells (Hamzic et al 2012), hepatocytes (Jayaraman et al 2005), endometrial carcinoma cells (Mannelqvist et al 2012), and erythroid progenitor cells (Miharada et al 2005).…”
Section: Lipocalin-2mentioning
confidence: 99%